Ganga: A subtle overview of names and glory in Sanskrit literature and the current scenario - Ambika Bhatt; Purnima Srivastava; Pavan kumar Yadav (Dr. Chinmay Pandya, 2023)
River Ganga is the largest river in India. It represents one of the magnificent geographical features of the country. It would be incorrect to confine it to say only as a water body. Nothing can match its everlasting divinity. It has its roots in Indian culture. As the holy river originates from "Gangotri Gomukh" in the country, it speaks much more about the culture, tradition, way of living of people. Since times immemorial, India has been called as the Land of Lords. It has been said to be brought from heaven and therefore it has been always personified as Goddess Ganga. River Ganga is Mother Ganga by all means. Since history enormous literature has been written from time to time about her greatness. Indian literature is largely enriched with her praise and appreciation. The action-oriented ganga offers a wide knowledge and wisdom to the people besides providing its pious water. As it fertiles the soil along the basin, it nourishes the souls and minds. Educating us in many ways and aspects, it gives us an overview of the structure of society. It teaches us how to lead an ideal life while maintaining a calm attitude. It teaches us to fulfil our responsibilities in our work area. Mother Ganga must be viewed with the spectacles of love, respect, emotions and dedication. Therefore, to structure the education in Indian perspectives the cognitive, affective and psychomotor properties of Holy Ganges can be inherited into the education process or it must be said that we should learn from Mother Ganga to become a balanced and an all-rounder personality.